Discovering the Repeatome of Five Species Belonging to the Asteraceae Family: A Computational Study - Maria Ventimiglia; Marco Castellacci; Gabriele Usai; Alberto Vangelisti; Samuel Simoni; Lucia Natali; Andrea Cavallini; Flavia Mascagni; Tommaso Giordani (Plants, 2023)
Genome divergence by repeat proliferation and/or loss is a process that plays a crucial role in species evolution. Nevertheless, knowledge of the variability related to repeat proliferation among species of the same family is still limited. Considering the importance of the Asteraceae family, here we present a first contribution towards the metarepeatome of five Asteraceae species. A comprehensive picture of the repetitive components of all genomes was obtained by genome skimming with Illumina sequence reads and by analyzing a pool of full-length long terminal repeat retrotransposons (LTR-REs). Genome skimming allowed us to estimate the abundance and variability of repetitive components. The structure of the metagenome of the selected species was composed of 67% repetitive sequences, of which LTR-REs represented the bulk of annotated clusters. The species essentially shared ribosomal DNA sequences, whereas the other classes of repetitive DNA were highly variable among species. The pool of full-length LTR-REs was retrieved from all the species and their age of insertion was established, showing several lineage-specific proliferation peaks over the last 15-million years. Overall, a large variability of repeat abundance at superfamily, lineage, and sublineage levels was observed, indicating that repeats within individual genomes followed different evolutionary and temporal dynamics, and that different events of amplification or loss of these sequences may have occurred after species differentiation.